Dispositivos Baseados em Microan??is Ressonadores para Sistemas de Comunica????es ??pticas - Neto, Josino (2022)
This dissertation aims to present the idealization of devices and/or photonic integrated circuits (PIC), based on micro-ring resonators (MRRs) and eligible for optical communications systems. First, a modulator for dense wavelength division multiplexing (DWDM) systems is exposed, based on the magneto-optic effect (MO). This circuit, in turn, is composed of two concentric MRRs, with the inner ring composed of a material of a magneto-optical nature, cerium substituted yttrium iron garnet (Ce:YIG). In the presence of an external magnetic field, Ce:YIG is able to change the resonant behavior of the outer ring, resulting, in turn, in the modulation effect (on/off) that is observed at the circuit output. In this work, the innovative approach in the design of high performance and small footprint modulators is highlighted. Additionally, an extinction rate (ER) value in the order of 46 dB was obtained, which is the highest value ever obtained to which we are aware, having as reference previous approaches also based on the MO effect. Finally, an ultra-wideband add/drop is exposed, based on two MRRs laterally side coupled to two straight waveguides. Stands out its ability to operate between the region of the optical spectrum comprised by ?? = 1250 nm and ?? = 1700 nm, above 400 nm. This device has an optimized free spectral range (FSR) in its central region of the spectrum equal to 40 nm, aiming to be used in coarse wavelength division multiplexing (CWDM) systems and in elastic optical networks (EONs) . The resonant behavior of MRRs is explored in this work.